Preparation method of Fe-doped NiCoZn-P / NF electrode material and application thereof

CN116905038BActive Publication Date: 2026-10-09NORTHEASTERN UNIV CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310946905.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2026-10-09
Estimated Expiration
2043-07-28

AI Technical Summary

Technical Problem

[0004]为了克服上述现有技术存在的缺陷,本发明针对贵金属催化剂价格昂贵、储量稀少等问题,提供了一种Fe掺杂NiCoZn-P/NF肼氧化辅助电解水制氢双功能电催化剂的制备方法

Benefits of technology

①本发明将Fe掺杂与Ni-P/Co-P/Zn-P异质结相结合,制备得到Fe掺杂NiCoZn-P/NF。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116905038B_ABST
    Figure CN116905038B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of Fe-doped NiCoZn-P / NF electrode material and application thereof, and the method is characterized in that: with the help of a hydrothermal method, nickel salt, cobalt salt and zinc salt are used as main salts to prepare nickel-cobalt-zinc-based hydroxide on the surface of a nickel foam; then, a small amount of Fe elements is doped by using an ion exchange method; finally, with the help of a phosphating method, a Fe-doped NiCoZn-P / NF catalyst with high catalytic activity and stability is obtained by adjusting parameters such as the content of a phosphating agent, a phosphating temperature, a heating rate and a phosphating time; and the catalyst is applied to hydrogen production by hydrazine oxidation assisted electrolysis of water, and is used as a bifunctional electrocatalyst for hydrazine oxidation reaction and hydrogen evolution reaction; the doping of Fe elements and the formation of a Ni-P / Co-P / Zn-P heterojunction can effectively increase the catalytic sites and catalytic activity of the catalyst, and the formation of the heterojunction can also effectively improve the stability of the material structure, so that the catalyst has excellent HzOR and HER catalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water electrolysis for hydrogen production technology, specifically relating to a method for preparing Fe-doped NiCoZn-P / NF electrode material and its application. Background Technology

[0002] The increasing depletion of fossil fuels and the growing prominence of environmental problems have led to a rapid increase in demand for green, environmentally friendly, and sustainable energy. Hydrogen energy, due to its high energy density (143 kJ·g⁻¹), is a promising option. -1 Hydrogen production, characterized by its zero pollution and renewability, is hailed as the core of the future global energy architecture and an ideal new energy source to replace fossil fuels. Compared to other traditional hydrogen production methods, water electrolysis has attracted significant attention due to its high conversion efficiency, high hydrogen purity, and relatively mature technology. Water electrolysis involves two half-reactions: the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Compared to HER, OER is a four-electron transfer reaction, and its slow kinetics are the main reason for the high energy consumption of water electrolysis. Recent studies have found that replacing the anode OER in water electrolysis with small-molecule oxidation reactions, such as the hydrazine oxidation reaction (HzOR), can significantly reduce the overpotential of water electrolysis. Furthermore, the hydrazine oxidation reaction can operate near room temperature, and more importantly, its products are only nitrogen and water. Noble metals Pt / C and RuO2 are currently the most effective electrocatalysts for HER and HzOR, respectively. However, the scarcity and high price of precious metals such as Pt / C and RuO2 limit their application. Therefore, it is imperative to study low-cost, high-activity, and high-stability inexpensive non-precious metal hydrazine oxidation-assisted water electrolysis for hydrogen production.

[0003] Transition metals nickel and cobalt, and their alloys, exhibit high HER and HzOR activity and stability. Among them, nickel-based phosphides have attracted particular attention due to their low cost and high HER and HzOR catalytic activity. To achieve efficient hydrazine oxidation-assisted water electrolysis for hydrogen production, the catalyst needs good conductivity. Furthermore, the hydrogen evolution performance of nickel-based phosphides can decline during prolonged water electrolysis due to changes in catalyst structure. Summary of the Invention

[0004] To overcome the shortcomings of existing technologies, this invention addresses the problems of high cost and scarcity of precious metal catalysts by providing a method for preparing a Fe-doped NiCoZn-P / NF hydrazine oxidation-assisted water electrolysis bifunctional electrocatalyst for hydrogen production. Heteroatom doping can effectively improve the conductivity and catalytic activity of the catalyst, while the design and synthesis of heterostructures can effectively improve the stability of the catalyst structure. Therefore, this invention prepares a Fe-doped NiCoZn-P / NF bifunctional electrocatalyst. Fe doping enhances the activity and conductivity of the active sites, while the construction of Ni-P / Co-P / Zn-P heterostructures further improves its catalytic activity and stability. Through their synergistic effect, a highly active and stable Fe-doped NiCoZn-P / NF hydrazine oxidation-assisted water electrolysis bifunctional catalyst for hydrogen production is obtained. This successfully achieves the goal of using transition metal electrodes instead of precious metal electrodes, effectively optimizing the catalytic activity and stability of the electrocatalyst, and has a very broad prospect for future practical applications.

[0005] To achieve the above-mentioned objective, this invention provides a method for preparing Fe-doped NiCoZn-P / NF electrode materials. The preparation method includes: firstly, synthesizing NiCoZn-OH on nickel foam by a hydrothermal method; then, doping Fe into it by an ion exchange method; and finally, obtaining a Fe-doped NiCoZn-P / NF bifunctional electrocatalyst with a nano-flower-shaped structure by a phosphating method.

[0006] In the above technical solution, further, the hydrothermal method involves dissolving zinc salt, cobalt salt, nickel salt, and urea sequentially in deionized water, wherein the zinc salt content is 0.5~100 g·L. -1 Cobalt salts 1~500 g·L -1 Nickel salts 1~500 g·L -1 Urea 1~100g·L -1 After stirring and dissolving, the solution is placed in a 50-200 mL reactor. The cleaned nickel foam is immersed in the solution and reacted at 80-150℃ for 4-24 h. The product obtained from the reaction is rinsed several times with deionized water and then placed in a vacuum drying oven and dried under vacuum at 60℃ for 6-24 h to obtain NiCoZn-OH / NF.

[0007] Furthermore, the ion exchange method involves dissolving iron salts in deionized water, with an iron salt solubility of 0.1~200 g·L. -1 The NiCoZn-OH / NF prepared above was then immersed in an iron salt solution of 10-500 mL for 5-120 min. The immersed NiCoZn-OH / NF was then placed in a vacuum drying oven and dried at 60 °C for 12-48 h to obtain Fe-doped NiCoZn-OH / NF.

[0008] Furthermore, the phosphating method involves placing the phosphating agent and Fe-doped NiCoZn-OH / NF upstream and downstream of a tube furnace, respectively, wherein the phosphating agent content is 0.1~5 g, and the mixture is heated at 2~10℃·min. -1 The temperature was increased to 250~450℃ at a heating rate and held for 0.5~5 h to obtain Fe-doped NiCoZn-P / NF.

[0009] Furthermore, the zinc salt is one or more of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, and zinc carbonate; the cobalt salt is one or more of cobalt sulfate, cobalt chloride, cobalt nitrate, cobalt acetate, and cobalt carbonate; and the nickel salt is one or more of nickel sulfate, nickel chloride, nickel nitrate, nickel acetate, and nickel carbonate.

[0010] Furthermore, the iron salt is one or more of ferric sulfate, ferric chloride, ferric nitrate, ferric acetate, and ferric carbonate.

[0011] Furthermore, the phosphating agent is one or more of sodium hypophosphite, potassium hypophosphite, and ammonium hypophosphite.

[0012] A Fe-doped NiCoZn-P / NF electrode material prepared by the above method.

[0013] Application of the aforementioned Fe-doped NiCoZn-P / NF electrode material in hydrazine oxidation-assisted water electrolysis for hydrogen production. Using a mercury oxide electrode as the reference electrode and a Pt sheet electrode as the counter electrode, the prepared Fe-doped NiCoZn-P / NF was used as the working electrode. Its HER and HzOR reactivity was tested in a three-electrode system using cathodic polarization curves (LSV), and its HER and HzOR stability was evaluated using constant current testing (E~t). Subsequently, Fe-doped NiCoZn-P / NF was used as both the cathode and anode in a two-electrode system to evaluate its hydrazine oxidation-assisted water electrolysis performance for hydrogen production. Under the test conditions, the hydrazine concentration in the alkaline hydrazine solution was 0.1–0.5 mol·L⁻¹. -1 KOH is 1 mol·L -1 The volume is 100mL.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: ①This invention combines Fe doping with Ni-P / Co-P / Zn-P heterojunction to prepare Fe-doped NiCoZn-P / NF.

[0015] ② In this invention, Fe doping can effectively improve the conductivity and catalytic activity of the catalyst, while the design and synthesis of heterostructures can effectively improve the stability of the catalyst structure.

[0016] ③ The Fe-doped NiCoZn-P / NF catalyst prepared in this invention has good HER and HzOR activity and stability, and excellent performance in hydrogen production by hydrazine oxidation-assisted water electrolysis.

[0017] ④ The raw materials used in this invention are inexpensive, readily available, and environmentally friendly. The synthesis method and process are simple, environmentally friendly, and controllable, and have the potential for large-scale industrial production. Attached Figure Description

[0018] Figure 1 This is a scanning electron microscope (SEM) image of the Fe-doped NiCoZn-P / NF in an embodiment of the present invention. Figure 2 This is a transmission electron microscope (TEM) image of Fe-doped NiCoZnP / NF in an embodiment of the present invention. Figure 3 The XRD pattern of Fe-doped NiCoZn-P / NF in this embodiment of the invention; Figure 4 X-ray photoelectron spectroscopy (XPS) of NiCoZn-P / NF and Fe-doped NiCoZn-P / NF. Figure 5 In this embodiment of the invention, the Fe-doped NiCoZn-P / NF catalyst is used in a solution containing 0.5 mol·L⁻¹ -1 Hydrazine and 1.0 mol·L -1 LSV spectrum of HzOR in potassium hydroxide mixed solution; Figure 6 In this embodiment of the invention, the Fe-doped NiCoZn-P / NF catalyst was used at 1.0 mol·L⁻¹. -1 LSV spectrum of HER in potassium hydroxide solution; Figure 7 In this embodiment of the invention, the Fe-doped NiCoZn-P / NF catalyst was used at 0.5 mol·L⁻¹ -1 hydrazine hydrate and 1.0 mol·L -1 LSV curve of hydrogen production by hydrazine oxidation-assisted water electrolysis in potassium hydroxide mixed solution (OHzS); Figure 8 shows the Fe-doped NiCoZn-P / NF catalyst in the embodiments of the present invention at 3.0 mol·L⁻¹ -1 hydrazine hydrate and 1.0 mol·L -1 E~t spectra in potassium hydroxide mixed solution: (a) HzOR (b) HER; Figure 9 The image shows the scanning electron microscope (SEM) morphology of NiCoZn-P / NF in the comparative example. Figure 10The X-ray diffraction (XRD) pattern of NiCoZn-P / NF in the comparative example is shown. Figure 11 For the comparative example, the NiCoZn-P / NF catalyst was prepared at a concentration of 0.5 mol·L⁻¹. -1 Hydrazine and 1.0 mol·L -1 LSV curve of HzOR in potassium hydroxide mixed solution; Figure 12 The NiCoZn-P / NF catalyst obtained in the comparative example was at 1.0 mol·L⁻¹ -1 LSV curve of HER in potassium hydroxide solution. Detailed Implementation

[0019] The present invention will be further described below with reference to specific embodiments, but this does not limit the invention in any way. To avoid redundancy, unless otherwise specified, the raw materials used in the following embodiments are all commercially available products, and the methods used are all conventional methods unless otherwise specified.

[0020] Example A method for preparing Fe-doped NiCoZn-P / NF electrode material and its application are disclosed. The preparation method includes: firstly, synthesizing NiCoZn-OH on nickel foam (NF) by hydrothermal method; then, doping Fe into it by ion exchange method; and finally obtaining Fe-doped NiCoZn-P / NF bifunctional electrocatalyst with nanoflower structure by phosphating method.

[0021] ①Preparation of NiCoZn-OH: 1.046 g nickel nitrate, 1.048 g cobalt nitrate, 0.536 g zinc nitrate and 0.542 g urea were dissolved in 45 mL deionized water, and then placed in a 100 mL reaction vessel. Cleaned nickel foam (NF) was immersed in the solution and reacted at 120 °C for 8 h. The product obtained from the reaction was repeatedly rinsed with deionized water several times and then placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain NiCoZn-OH / NF.

[0022] ② Preparation of Fe-doped NiCoZn-OH: Weigh 0.440 g of ferric nitrate and dissolve it in 100 mL of deionized water. Immerse the NiCoZn-OH / NF precursor prepared in step ① into the above iron salt solution. After reacting for 5 min, rinse repeatedly with deionized water. Then, place the soaked NiCoZn-OH / NF into a vacuum drying oven and dry at 60℃ for 12 h to obtain Fe-doped NiCoZn-OH / NF.

[0023] ③ Preparation of Fe-doped NiCoZn-P / NF: 0.5 g of sodium hypophosphite and the Fe-doped NiCoZn-OH / NF prepared in step ② were placed upstream and downstream of the inlet of a tube furnace, respectively, and incubated at 5 °C·min. -1 The temperature was increased to 300°C at a heating rate of 1 h, and the phosphating time was 1 h, thereby obtaining the Fe-doped NiCoZn-P / NF of the example.

[0024] Structural characterization of Fe-doped NiCoZn-P / NF catalysts: Figure 1 and 2 The images shown are SEM and TEM images of the Fe-doped NiCoZn-P / NF catalyst. Figure 1 It can be seen that Fe-doped NiCoZn-P / NF is composed of nanoflora-like structures assembled from nanospikes. Figure 2 High-resolution TEM shows that Fe-doped NiCoZn-P / NF mainly contains the (211) and (220) crystal planes of Zn3P2, the (201), (111) and (210) crystal planes of Ni2P, and the (111), (210) and (201) crystal planes of Co2P. Figure 3 The image shows the XRD pattern of Fe-doped NiCoZn-P / NF. Figure 3 It can be seen that the Fe-doped NiCoZn-P / NF catalyst still consists of three phases: Ni2P, Co2P, and Zn3P2, which is consistent with... Figure 2 The obtained TEM results correspond to this. Figure 10 Compared to the XRD patterns of NiCoZn-P / NF in the comparative example. Figure 3 The XRD patterns of Fe-doped NiCoZn-P / NF show that the peak positions of the three phases Ni2P, Co2P and Zn3P2 shift to the right to varying degrees, which is related to the lattice distortion caused by Fe doping. Figure 4 This shows the XPS spectra of NiCoZn-P / NF and Fe-doped NiCoZn-P / NF (Fe-NiCoZn-P / NF). (Source: [Insert source here]) Figure 4 It can be seen that the XPS spectra of both NiCoZn-P / NF and Fe-doped NiCoZn-P / NF catalysts showed peaks of Ni 2p, Co 2p and Zn 2p. At the same time, Fe-doped NiCoZn-P / NF also showed a peak of Fe 2p, which confirms the successful doping of Fe.

[0025] Performance testing of Fe-doped NiCoZn-P / NF hydrazine oxidation-assisted water electrolysis for hydrogen production: Figure 5 This indicates that the Fe-doped NiCoZn-P / NF catalyst at 0.5 mol·L⁻¹ -1 Hydrazine and 1.0 mol·L -1The LSV spectrum of HzOR in a potassium hydroxide mixed solution, with a scan rate of 5 mV·s. -1 .Depend on Figure 5 It can be seen that the Fe-doped NiCoZn-P / NF catalyst exhibits excellent HzOR catalytic activity, with a peak performance at 1000 mA·cm⁻¹. -2 The oxidation potential of hydrazine at the current density is 315 mV. Figure 6 This indicates that the Fe-doped NiCoZn-P / NF catalyst at 1.0 mol·L⁻¹ -1 LSV spectrum of HER in potassium hydroxide, scan rate 5 mV·s -1 .Depend on Figure 6 It can be seen that the Fe-doped NiCoZn-P / NF catalyst exhibits excellent HER catalytic activity at 1000 mA·cm⁻¹. -2 The hydrogen evolution potential at the current density is 118 mV. (Compared to the comparative example) Figure 11 and Figure 12 Compared with the obtained data, the successful doping of Fe element significantly improved the catalytic activity of NiCoZn-P / NF for HzOR and HER. Figure 7 This represents a two-electrode full electrolysis water performance test using an Fe-doped NiCoZn-P / NF catalyst as both the cathode and anode. Figure 7 It can be seen that when the electrolyte does not contain hydrazine, its performance at 100 mA·cm⁻¹ is... -2 The water decomposition voltage of the fully electrolyzed water system (OWS) at current density is 1.95 V; with the addition of hydrazine molecules, the water decomposition voltage of the hydrazine oxidation-assisted fully electrolyzed water system (OHzS) is 0.38 V, a decrease of 1.57 V, which confirms the energy-saving effect of hydrazine oxidation-assisted water electrolysis for hydrogen production. Figure 8a This indicates that the Fe-doped NiCoZn-P / NF catalyst is at 3.0 mol·L⁻¹ -1 Hydrazine and 1.0 mol·L -1 The HzOR stability of a potassium hydroxide mixed solution was tested using the potential-time curve (E~t) in a three-electrode system. Figure 8a It can be seen that the Fe-doped NiCoZn-P / NF catalyst at 100 mA·cm⁻¹ -2 After a long test at current density for 120 h, its HzOR catalytic potential did not change much, confirming its good HzOR catalytic stability. Figure 8b This indicates that the Fe-doped NiCoZn-P / NF catalyst at 1.0 mol·L⁻¹ -1 In potassium hydroxide solution, the HER stability test results were obtained using the potential-time curve (E~t) in a three-electrode system. Figure 8b It can be seen that the Fe-doped NiCoZn-P / NF catalyst at 100 mA·cm⁻¹-2 After a long-term test at current density for 120 h, its HER catalytic potential did not change much, which also confirms its excellent HER catalytic stability.

[0026] Comparative Example A method for preparing a NiCoZn-P / NF electrocatalyst and its application in hydrazine oxidation-assisted water electrolysis for hydrogen production includes the following steps: (1) Preparation of NiCoZn-OH: 1.046 g nickel nitrate, 1.048 g cobalt nitrate, 0.536 g zinc nitrate and 0.542 g urea were dissolved in 45 mL deionized water and then placed in a 100 mL reaction vessel. The cleaned NF was immersed in the solution and reacted at 120 °C for 8 h. The product obtained from the reaction was repeatedly rinsed with deionized water several times and then placed in a vacuum drying oven and vacuum dried at 60 °C for 8 h to obtain NiCoZn-OH / NF.

[0027] (2) Preparation of NiCoZn-P / NF: 0.5g of sodium hypophosphite and the NiCoZn-OH prepared in step (1) were placed upstream and downstream of the gas inlet of a tubular furnace, respectively, and heated at 5℃·min -1 The temperature was increased to 300℃ at a heating rate of 1 h, and the phosphating time was 1 h, thus obtaining the control sample NiCoZn-P / NF.

[0028] (3) Structural characterization of NiCoZn-P / NF catalyst: Figure 9 Scanning electron microscopy (SEM) images of the NiCoZn-P / NF catalyst. Figure 9 It is known that NiCoZn-P / NF exhibits a porous nanosheet structure. The porous structure composed of nanosheets can provide more catalytic active sites and can also promote the transport and diffusion of reactants and products. Figure 10 The XRD pattern of the NiCoZn-P / NF material. Figure 10 It can be seen that the NiCoZn-P / NF catalyst is mainly composed of three phases: Ni2P, Co2P and Zn3P2.

[0029] (4) Performance test of NiCoZn-P / NF hydrazine oxidation-assisted water electrolysis for hydrogen production: Figure 11 This indicates that the NiCoZn-P / NF catalyst is at 0.5 mol·L⁻¹ -1 Hydrazine and 1.0 mol·L -1 The LSV spectrum of HzOR in a potassium hydroxide mixed solution, with a scan rate of 5 mV·s. -1 .Depend on Figure 11 It can be seen that the NiCoZn-P / NF catalyst has high HzOR catalytic activity, which is at 800 mA·cm⁻¹. -2The oxidation potential of hydrazine at the current density is 384 mV. Figure 12 This indicates that the NiCoZn-P / NF catalyst at 1.0 mol·L⁻¹ -1 LSV spectrum of HER in potassium hydroxide, scan rate 5 mV·s -1 .Depend on Figure 12 It can be seen that the NiCoZn-P / NF catalyst has high HER catalytic activity, which is achieved at 800 mA·cm⁻¹. -2 The hydrogen evolution potential at the current density is 221 mV.

[0030] For anyone skilled in the art, many possible variations and modifications can be made to the technical solutions of this invention, or equivalent embodiments can be modified based on the disclosed technical content, without departing from the scope of the technical solutions of this invention. Therefore, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of this invention without departing from the content of the technical solutions of this invention should still fall within the protection scope of the technical solutions of this invention.

Claims

1. A method for preparing Fe-doped NiCoZn-P / NF electrode material, characterized in that, The preparation method includes: firstly, synthesizing NiCoZn-OH on nickel foam by hydrothermal method, then doping Fe into it by ion exchange method, and finally obtaining Fe-doped NiCoZn-P / NF bifunctional electrocatalyst with nanoflower structure by phosphating method.

2. The preparation method according to claim 1, characterized in that, The hydrothermal method involves dissolving zinc salt, cobalt salt, nickel salt, and urea sequentially in deionized water; wherein the zinc salt content is 0.5~100 g·L⁻¹. -1 Cobalt salts 1~500 g·L -1 Nickel salts 1~500g·L -1 Urea 1~100 g·L -1 After stirring and dissolving, the solution is placed in a 50-200 mL reactor. The cleaned nickel foam is immersed in the solution and reacted at 80-150℃ for 4-24 h. The product obtained from the reaction is rinsed several times with deionized water and then placed in a vacuum drying oven and dried under vacuum at 60℃ for 6-24 h to obtain NiCoZn-OH / NF.

3. The preparation method according to claim 1, characterized in that, The ion exchange method involves dissolving iron salts in deionized water at a concentration of 0.1–200 g·L⁻¹. -1 The prepared NiCoZn-OH / NF was then immersed in an iron salt solution of 10-500 mL for 5-120 min. The immersed NiCoZn-OH / NF was then placed in a vacuum drying oven and dried at 60 °C for 12-48 h to obtain Fe-doped NiCoZn-OH / NF.

4. The preparation method according to claim 1, characterized in that, The phosphating method is as follows: A phosphating agent and Fe-doped NiCoZn-OH / NF are placed upstream and downstream of a tube furnace, respectively, wherein the phosphating agent content is 0.1~5g, and the furnace is heated at 2~10℃·min. -1 The temperature was increased to 250~450℃ at a heating rate and held for 0.5~5 h to obtain Fe-doped NiCoZn-P / NF.

5. The preparation method according to claim 2, characterized in that, The zinc salt is one or more of zinc sulfate, zinc chloride, zinc nitrate, and zinc acetate; the cobalt salt is one or more of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate; and the nickel salt is one or more of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate.

6. The preparation method according to claim 3, characterized in that, The iron salt is one or more of ferric sulfate, ferric chloride, and ferric nitrate.

7. The preparation method according to claim 4, characterized in that, The phosphating agent is one or more of sodium hypophosphite, potassium hypophosphite, and ammonium hypophosphite.

8. An Fe-doped NiCoZn-P / NF electrode material prepared by the method described in any one of claims 1-7.

9. The application of the Fe-doped NiCoZn-P / NF electrode material as described in claim 8 in hydrazine oxidation-assisted water electrolysis for hydrogen production.

Citation Information

Patent Citations

  • Foamed nickel self-supporting FeCo phosphide electrocatalyst, preparation method and application thereof

    CN112774704A